Ocena atrakcyjności szkół językowych z wykorzystaniem wybranych metod wielowymiarowej analizy statystycznej - Kurzydłowski, Adam; Zaborski, Artur (The Assessment of the Attractiveness of Language Schools by Multivariate Methods, 2005)
The paper presents results of the research which carried in five biggest language schools in Jelenia Gora. The aim of analysis was the identification of factors which determined the choice of school and evaluation of market position of the selected schools. The research was conducted by means of two methods of multivariate statistical analysis: classification trees and multidimensional scaling.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 453-461